Environmentally-conscious cities: Energy transformation through ecoregional planning and carbon trading for sustainable regional development - Falah, Khoirul (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The global climate crisis and dependency on fossil fuels pose serious threats to food, water, and energy security in Indonesia, particularly in ecologically and economically strategic regions such as Garut Regency. This research proposes an integrated strategy for sustainable regional development based on ecoregional planning and carbon trading, addressing spatial inequality, environmental degradation, and clean energy transformation. Methods: Spatial-territorial analysis and participatory cross-sectoral policy review serve as the primary methodology, supplemented by stakeholder interviews and geospatial assessments. Findings: The findings reveal significant renewable energy potential in Garut, including geothermal (PLTP Darajat), solar, micro-hydro, and biomass from agricultural waste. However, 52.57% land-use misalignment, a 42.46% decline in forest area, and water deficits in 19 sub-districts endanger ecosystem stability and local economic resilience. Strategic ecoregional planning, including environmental carrying capacity-based zoning, 45% protected area retention, and renewable energy integration into spatial plans, can reverse these negative trends. Implementation requires multi-sectoral collaboration involving government, private sector, and communities, supported by green technologies and innovative financing (APBD, KPBU, CSR). The environmental benefits encompass biodiversity conservation, enhanced climate resilience, and emission reductions toward the net-zero emissions 2045 target. Conclusion: This study concludes that Garut’s transformation into an energy-independent, socially equitable, and ecologically resilient region can serve as a national model for achieving the Golden Indonesia 2045 vision. Novelty/Originality of this article: The novelty of this article lies in proposing an integrated ecoregional planning and carbon trading framework as a scalable model for aligning spatial planning, renewable energy development, and socio-political risk management in regional sustainability transitions.